Revisiting TAM polarization: beyond M1- and M2-type TAM toward clinical precision in macrophage-targeted therapy - Qingqing Wang; Wenxue Ma (Experimental and Molecular Pathology)
Tumor-associated macrophages (TAMs) are key regulators of the tumor microenvironment (TME), significantly influencing cancer progression and therapeutic responses. TAMs polarize into M1 or M2 phenotypes, exerting distinct functional roles. M1-type macrophages promote inflammation and tumor cell destruction, whereas M2-type macrophages facilitate immune suppression, angiogenesis, and metastasis. However, inconsistencies and mischaracterizations in the literature regarding TAM classification have led to confusion in the field, potentially impeding the development of effective macrophage-targeted immunotherapies. This commentary highlights the need for clear and standardized nomenclature, clarifies the functional distinctions between M1- and M2- type TAMs, and explores the signaling pathways and environmental factors driving their polarization. We also discuss emerging TAM subtypes and the therapeutic significance of accurate classification, including macrophage reprogramming strategies. Standardizing terminology and addressing misconceptions will be critical to advancing macrophage-based immunotherapies and improving clinical outcomes in cancer treatment.